2018
DOI: 10.1111/cen.13611
|View full text |Cite
|
Sign up to set email alerts
|

Treatment choice, satisfaction and quality of life in patients with Graves’ disease

Abstract: Patient satisfaction with therapy and QoL does not differ by treatment type. Therefore, clinical and social factors, in combination with patient choice and resource availability, should determine which treatment modality patients with Graves' disease should receive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…In another survey-based study, 23% who were treated with surgery mentioned 'radioactive nature of the treatment' as one of the reasons for not choosing RAI. This was corroborated in a study in which 'preference to avoid RAI' was the most commonly reported reason for choosing surgery (34). In patients treated with RAI, the pre-treatment concerns significantly decreased after treatment, suggesting the absence of long-term concerns (32,41).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In another survey-based study, 23% who were treated with surgery mentioned 'radioactive nature of the treatment' as one of the reasons for not choosing RAI. This was corroborated in a study in which 'preference to avoid RAI' was the most commonly reported reason for choosing surgery (34). In patients treated with RAI, the pre-treatment concerns significantly decreased after treatment, suggesting the absence of long-term concerns (32,41).…”
Section: Discussionmentioning
confidence: 62%
“…Insufficient data is available on the treatment preferences of patients with GD. Previous studies have focused on surgery versus RAI treatment or used non-validated instruments (32,33,34). The concordance of preferences between both patients and clinicians has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to some adult studies which have demonstrated that patients who have had a thyroidectomy for Graves’ disease report an improvement in QoL compared with those on prolonged ATD, 28,29 and a recent study which reported that RI‐treated adults had worse thyroid‐related and general QoL than those treated with ATD or thyroidectomy 11 . However, other adult studies have shown equal satisfaction and QoL improvement with all treatment modalities 13,30 …”
Section: Discussionmentioning
confidence: 79%
“…11 However, other adult studies have shown equal satisfaction and QoL improvement with all treatment modalities. 13,30 In our cohort of young people, around half said that they did not feel fully recovered from Graves' disease despite at least a year of treatment, including half of those whom had already received definitive treatment. This compares to a figure of around 25% in the adult population who did not feel fully recovered 6-10 years following treatment for Graves' disease.…”
Section: Discussionmentioning
confidence: 97%
“…Thyrotoxicosis, most often caused by GD, potentially caused severe symptoms and is associated with premature mortality, primarily related to cardiovascular events. 11 Due to its progressiveness, early detection of the disease is vital to identify affected individuals and to prevent or reduce the risk of having a severe case of GD. Therefore, the development of rapid and cost‐effective methods for screening and monitoring GD progression is indispensable.…”
Section: Discussionmentioning
confidence: 99%